The Effect of Investing Policy Ratio, Net Profit Margin, Loan to Deposit Ratio and Return on Asset on Capital Adequacy Ratio in Banking Companies Listed in The Indonesia Stock Exchange - Fanny Dewi Lie Gunardy; Melisa Cantika Dewi; Siti Dini; Anggono Anggono (International Journal of Economics Development Research (IJEDR), 2023)
The aim of this research is to examine the influence of Investment Policy Ratio, Net Profit margin, loan to Deposit Ratio, Return on Assets and Capital Adequacy Ratio. In this research, researchers used quantitative research methods. The population used in the research was 53 banking companies and a sample of 29 banks with a total of 87 observations. The data analysis techniques used multiple linear regression analysis with SPSS version 26. The research results show that the Investing Policy Ratio and Net Profit Margin have no effect on the Capital Adequacy Ratio. Loan to Deposit Ratio has a positive and significant effect on the Capital Adequacy Ratio. Return on Assets has a negative and significant effect on the Capital Adequacy Ratio. Investing Policy Ratio, Net Profit Margin, Loan to Deposit Ratio and Return on Assets simultaneously have a positive and significant effect on the Capital Adequacy Ratio in banking companies listed on the Indonesia Stock Exchange. The determination size of 14.4% means that the Investing Policy Ratio, Net Profit Margin, Loan to Deposit Ratio and Return on Assets can explain the Capital Adequacy Ratio in banking companies listed on the Indonesia Stock Exchange.